High-Resolution Differential Thermography of Semiconductor Edifices - Vera Marie Sastine; Vernon Julius Cemine; Carlo Mar Blanca; Caesar Saloma (Science Diliman, 2004)
We develop a cost-effective, high-resolution, and noninvasive imaging technique for thermal mapping of semiconductor edifices in integrated circuits. Initial implementation was done using a power-stabilized optical feedback laser system that detects changes in the optical beam-induced current when the package temperature of the device is increased. The linear change in detected current can be translated to a thermal gradient, which can reveal semiconductor “hotspots”—localized sites with anomalous thermal activity. These locales are possible fault sites or areas susceptible to defects, which are the best jump-off points for failure analysis.